Exploratory rivaroxaban trial for isolated calf deep vein thrombosis with a risk factor of thrombosis extension: an open-label, multicenter, randomized controlled trial - Yoshito Ogihara; Norikazu Yamada; Daisuke Izumi; Yuichi Sato; Toru Sato; Hitoshi Nakaya; Tatsuya Mori; Satoshi Ota; Midori Makino; Toru Ogura; Satoshi Tamaru; Yuki Nishimura; et al. (Research and Practice in Thrombosis and Haemostasis, 2024)
Background: Limited evidence exists regarding the incidence of recurrent venous thromboembolism (VTE) in patients diagnosed with isolated distal deep vein thrombosis (DVT) who are at risk of thrombosis extension whether they receive anticoagulation therapy or not. Objectives: The study aimed to investigate the incidence of recurrent VTE and the impact of rivaroxaban in this patient population. Methods: This open-label, exploratory, and randomized controlled trial was conducted at 7 centers in Japan between April 2019 and April 2022. Adult patients with isolated distal DVT at risk of thrombosis extension received either rivaroxaban combined with physical therapy or physical therapy alone for 90 days. Whole-leg ultrasound was performed at 14 and 90 days. We assessed a composite outcome of symptomatic or asymptomatic proximal DVT or symptomatic pulmonary embolism as the primary outcome until the end of the treatment period using an intention-to-treat analysis. Major bleeding was evaluated as a key secondary outcome. Results: Out of 90 enrolled patients, 3 were excluded due to withdrawal of consent; therefore, we analyzed 87 participants. The rivaroxaban group (n = 42) reported no primary outcomes (0%; 95% CI, 0.0%-8.4%), whereas the physical therapy group (n = 45) had 2 cases of symptomatic proximal DVT (4.4%; 95% CI, 0.5%-15.1%). Major bleeding events occurred in 4 patients in the rivaroxaban group (9.5%; 95% CI, 2.7%-22.6%), whereas no events occurred in the physical therapy group (0%; 95% CI, 0%-7.9%). Conclusion: Preliminary data suggest that rivaroxaban may reduce the risk of VTE recurrence among this patient subset, albeit with an increased incidence of bleeding events.